FEATURES OF TEACHING RUSSIAN AS A FOREIGN LANGUAGE IN TECHNICAL UNIVERSITIES (American Journal of Pedagogical and Educational Research, 2023)
Тhe article is devoted to the specifics of teaching the Russian language in technical universities of the Republic of Uzbekistan. The analysis of actual problems of teaching the Russian language to students of engineering specialties is carried out. The importance of maintaining students' motivation to study Russian as a foreign language is noted. The ways to increase motivation and interest in the subject of study are listed. The methods of using information and communication technologies in the process of teaching the Russian language are considered. The importance of studying the Russian language both at the general level and at the level of special technical and scientific terminology is emphasized.